An approach to malignant mammary phyllodes tumors detection - Ilić Ivan; Ranđelović Pavle; Ilić Ratko; Katić Vuka; Milentijević Maja; Veličković Ljubinka; Krstić Miljan (Vojnosanitetski Pregled)
Background/Aim. Mammary phyllodes tumors (MPT) are uncommon fibroepithelial (biphasic) neoplasms whose clinical behavior is difficult to predict on the basis of histological criteria only. They are divided into benign, borderline malignant and malignant groups. Sometimes it appears difficult to distinguish these tumors from other types of soft tissue sarcomas. Because of the relatively scant data on the role of biological markers in MPT histogenesis, we have decided to undertake the following study, trying to shed more light on the issue by investigating the following elements that make up MPT: their histological patterns, biological behavior, enzymohistochemical, histochemical and immunohistochemical characteristics (ICH) together with the mast cell analysis. Methods. We examined the biopsy material of 35 MPT in our laboratory. Enzymohistochemistry was performed on frozen sections (method of Crowford, Nachlas and Seligman). The used methods were classical hematoxylin-eosin (H&E); histochemical Massontrichrome, Alcian-blue, Periodic acid Schiff and immunohistochemical LSAB2 method (DacoCytomation). Ki-67, ckit, vimentin, estrogen receptor (ER), progesterone receptor (PR) and Her-2 oncoprotein immunohistochemistry was performed on all tumors. Results. The patients were ranged per age from 30-62 years (mean 43.3 years, median 39 years). A total of 35 cases of MPT were included: 20 benign (57%), 6 borderline malignant (17%) and 9 malignant (26%). Twenty-two patients (62.8 %) underwent segmental mastectomy, while 13 (37.2%) had total mastectomies. Twenty-eight patients had negative surgical margins at original resection. The mean size of malignant MPT (7.8 cm) was larger than that of benign MPT (4.5 cm). Significant features of the malignant MPT were: stromal cellularity, stromal cellular atypism, high mitotic activity, atypic mitoses, stromal overgrowth, infiltrative tumor contour and heterologous stromal elements. Benign MPT showed strong enzymohistochemical Leucine Amino Peptidase (LAP) activity in both epithelial and stromal components while it was weak or absent in the epithelial parts of the malignant tumors. Acid mucopolysacharides were present in the stromal component of all types of these tumors. Benign MPT had a lower Ki-67 than did borderline malignant MPT (4 versus 28). Malignant MPT had a greater than 8-fold higher Ki-67 activity than did benign tumors (35 versus 4). Intracytoplasmatic c-kit expression was associated with a pathological diagnosis of malignant MPT, correlating with increasing grade (p < 0.05). In hypercellular stroma of borderline malignant and especially malignant forms of MPT, high activity of ER in mast cells was confirmed. Oncoprotein Her-2 activity, mostly in epithelial components, correlated with the degree of malignant progression of MPT (p < 0.05). Conclusion. Besides the well-known malignant features additional parameters have been found to be high Ki-67 and ckit stromal expressions, and weak LAP activity in the epithelial part of malignant MPT, as well as mast cells with a high expression of ER.